Pengaruh Kompensasi Finansial Terhadap Semangat Kerja Karyawan PT Surya Perdana Agung Pekanbaru - Lamin, Lamin (Sekolah Tinggi Ilmu Ekonomi Riau, 2023)
This study aims to determine the effect of the Effect of Financial Compensation on the morale of the employees of PT. Surya Perdana Agung Pekanbaru. In this study, data were collected through questionnaires distributed to 34 respondents. Quantitative analysis included validity and reliability tests, classical assumption tests, hypothesis testing through t-test and analysis of coefficient of determination (R2). The data that has met the validity test, reliability test, and classical assumption test are processed to produce a regression equation. a. SPSS results obtained that t count 4.861 > t table 2.036. Also the significance level is 0.00 < 0.05. So the results of the hypothesis test in this study are that financial compensation has a significant effect on the morale of the employees of PT. Surya Perdana Agung Pekanbaru. The value of R-square (Coefficient of Determinant) is 0.425, it can be interpreted that the influence of the financial compensation variable on the morale of the employees of PT. Surya Perdana Agung Pekanbaru is 42.50%. The relationship between financial compensation and employee morale at PT. Surya Perdana Agung Pekanbaru is positive, as evidenced by the regression coefficient (b) of 0.571, which means that each increase in financial compensation of one unit will increase the morale of the employees of PT. Surya Perdana Agung Pekanbaru amounted to 0.571 units.